Organoleptic Study of Mangrove Pudding from Sonneratia alba Fruit - Wintah Wintah; Kiswanto Kiswanto (Journal of Nutrition Science, 2024)
Sonneratia alba is a mangrove species that grows in areas with salinity and is usually located in estuarine areas. Sonneratia alba produces fruit that can be used as an additional ingredient for making pudding. Previously there has been no study of organoleptic studies of Sonneratia alba pudding. Therefore, it is necessary to study the organoleptic of mangrove pudding from Sonneratia alba fruit. The organoleptic test consists of hedonic tests of taste, colour, aroma, and texture. Sonneratia alba pudding is made several treatments. The results of the hedonic test of Sonneratia alba pudding most preferred by panellists were in sample P2 with the composition of the ratio between Sonneratia alba juice 20% and agar flour 30%. Hedonic test results of taste (4.85), colour (4.62), scent (4.67), and texture (4.68).